Prediction of hematopoietic stem cell yield after mobilization with granulocyte–colony‐stimulating factor in healthy unrelated donors. Issue 12 (16th July 2015) - Teipel, Raphael; Schetelig, Johannes; Kramer, Michael; Schmidt, Helmuth; Schmidt, Alexander H.; Thiede, Christian; Oelschlägel, Uta; Kroschinsky, Frank; Bornhäuser, Martin; Ehninger, Gerhard; Hölig, Kristina
Abstract : BACKGROUND: The collection of hematopoietic stem cells from the peripheral blood of healthy donors has been established as a highly efficient method. Nevertheless, some donors have a moderate or poor chance of harvest success with standard mobilization regimens. STUDY DESIGN AND METHODS: We retrospectively reviewed data from 7216 unrelated healthy donors, who underwent granulocyte–colony‐stimulating factor mobilization and consecutive leukapheresis for allogeneic stem cell transplantation. We tested different donor variables of potential influence and established a statistical model for prediction of upfront mobilization capacity and harvest success. In addition, we calculated the likelihood of a successful harvest dependent on predicted preapheresis CD34+ count and recipient weight. RESULTS: Female sex, older age, smoking, elevated lactate dehydrogenase, higher relative lymphocyte count, and higher large unstained cell count at baseline were negatively correlated with the CD34+ cell count on Day +5 (p < 0.0001). In contrast, higher platelet count, higher body mass index, higher absolute lymphocyte count, and higher relative monocyte count at baseline showed a positive correlation with the CD34+ count on Day +5 (p < 0.0001). Using a model built on these factors, we could significantly improve the prediction of harvest success compared to a basic model. CONCLUSION: The model allows the identification of female donors who eventually have a significant risk of harvest failure if requested to donate for recipients with a high body weight.